Exploring the determinant factors of food related fatwa issuances based on ‘urf - Ruzulan, Zulaipa; Ab. Rahman, Suhaimi; Saidon, Rafeah; Fathullah Harun, Hanifah Musa (E-International Publishing House, 2020)
There are queries on the halal status of food among Muslim consumers due to the accessibility of halal knowledge via mass media, and this needs for the jurists’ clarification (fatwa). Thus, this paper seeks to examine the determinant factors of fatwa’s decisions on food-related issues based on the approach of ‘urf. A qualitative approach which involved document analysis technique was applied from various authoritative sources. Furthermore, content analysis and constant comparative methods were used to analyze the data. This study will assist policymakers in dealing with food-related issues and help the public in identifying the rationale of the fatwa’s decisions.